Performance Evaluation of Costs and Schedules for the Merah Putih Cooperative Construction Project Using Earned Value Management - Suriyanto Suriyanto; Ahmad Purkon; Wiwin Aswawarman; Try Sugiyarto Soeparyanto; Abdul Kadir (ADI Bisnis Digital Interdisiplin Jurnal, 2026)
Time and cost control are important aspects in the implementation of construction projects. This study aims to analyze the performance of construction projects using the Earned Value Management (EVM) method through evaluations of three sample villages in the development of the Red and White Cooperative Outlet in South Konawe, namely projects experiencing delays, projects that are running according to schedule and projects that are completed in the 2nd month, from a 3-month duration. The data used is a contract value of Rp1,600,000,000 with 90 working days. The evaluation was carried out in the 2nd month by analyzing earned value management indicators which include budgeted cost of work scheduled (BCWS), budgeted cost of work performed (BCWP), actual cost of work performed (ACWP), cost variance (CV), schedule variance (SV), cost performance index (CPI), schedule performance index (SPI), estimate to complete (ETC), estimate at completion (EAC), estimate temporary schedule (ETS), and estimate at schedule (EAS). The results of the study showed that the evaluation of the project that experienced delays obtained an SPI value of 0.92 and a CPI of 0.96 which indicated delays in work implementation and cost wastage, with a predicted project completion of 92.6 days or 2.6 days. Earned Value Management method is able to provide information regarding the condition of the project from the cost and time aspects, so that it can be used as a tool for controlling and evaluating construction project performance.